DESIGN, DYNAMIC MODELING AND CONTROL OF WEARABLE FINGER ORTHOSIS - Tasar, Beyda; Tatar, Ahmet Burak; Tanyildizi, Alper Kadir; Yakut, Oguz (World Scientific Publ Co Pte Ltd, 2021)
Human hands and fingers are of significant importance in people's capacity to perform daily tasks (touching, feeling, holding, gripping, writing). However, about 1.5 million people around the world are suffering from injuries, muscle and neurological disorders, a loss of hand function, or a few fingers due to stroke. This paper focuses on newly developed finger orthotics, which is thin, adaptable to the length of each finger and low energy costs. The aim of the study is to design and control a new robotic orthosis using for daily rehabilitation therapy. Kinematic and dynamic analysis of orthosis was calculated and the joint regulation of orthosis was obtained. The Lagrange method was used to obtain dynamics, and the Denavit-Hartenberg (D-H) method was used for kinematic analysis of hand. In order to understand its behavior, the robotic finger orthotics model was simulated in MatLab/Simulink. The simulation results show that the efficiency and robustness of proportional integral derivative (PID) controller are appropriate for the use of robotic finger orthotics.
Keywords: Finger orthosis; therapy robot; real-time PID; rehabilitation